Proposal to Reduce Transfer Time Through a Multimodal Interconnection Model - Ramos Illaconza, Oscar Gianfranco (2025)
Transferring commuters on Atocongo (Lima, Perú), between Linea Amarilla (buses) and Line 1 of the Lima Metro (subway) shows various challenges. Commuters have to board the buses on the street, after crossing crowded roads, there are also interruptions like street vendors, crowded sidewalks, and lack of traffic signals at crosswalks. The transfer time is not optimized and the actios is not safe for commuters. This research proposes a multimodal interconnection that reduces transfer time and leads users directly between both transportation systems, on both routes: From Santiago de Surco (SS) and San Juan de Miraflores (SJM). The transfer time was obtained (current situation) and a model was developed with the interconnection infrastructure of both transport systems (proposed situation). From the comparison of both situations, it was obtained that the times were reduced, for the route from SS 49.87% and for the route from SJM 28.87%. It is concluded that the proposed model manages to reduce the user's transfering time.